The extent of the legitimacy of international intervention for humanitarian considerations within the framework of the principle of inadmissibility of the United Nations interference in the heart of the internal authority of states - هادي, هادي طلال (Journal of Legal Sciences, 2020)
The international humanitarian intervention regardless its legitimacy and illegitimacy aims at using the armed and unarmed force to Protect the rights of the human being and his/ her fundamental freedom when heavy violations may occur for these rights and the interferences features and their development appeared during the period that happened after the cold war as well as the establishment of the new international system the is based on the respect of the human rights to achieve the global peace and security.The international practices proved that the international humanitarian intervention which have been practiced do not rely on any legal justification and sometimes it forms assault against the states' rights and their internal sovereign as the interference which has been practiced by the American administration in sumal and Lybia and other countries thus such interference is described by the international humanitarian interference in some cases as duality and is away from the international laws and rules.The concept of the non- interference in the states interior affairs affirms on the states and their interior entities It is seen that the concept of respecting the human rights and his/ her essential freedom urges the global states and organizations in particular to feel the necessity of the interference in order to keep these rights and prevent attacking them and this puts the two principles contradicted legally as far as legitimacy is concerned which is practiced by the states that practice the international humanitarian interference and this would be discussed in the research paper.